Slovene national identity as a part of Yugoslav identity or asits contradiction? - Podhajská, Terézia (Études sur la Région Méditerranéenne, 2020)
National identity plays an essential part in the development of the idea of every nation’s self-determination and national history. National identity is a complex concept, which is not easy to define, especially within the context of modern, multinational states of the central European area, such as Czechoslovakia or the Kingdom of Serbs, Croats and Slovenes, which afterwards became Yugoslavia. The new state of Yugoslavia was one of the most diverse and heterogeneous countries of Europe, which united these three nations. Besides Croats and Serbs the Slovenians also developed their national identity before Yugoslavia. The present study examines the duality of the national identity of the Slovene people within the context of the Kingdom of Serbs, Croats and Slovenes, during the interwar period of 20th century. The Slovenes willingly accepted the Yugoslav unification, which earned them protection from threatening neighbouring states. However, the unitarian concept of Yugoslavism started to clash with the multinational, multi-ethnic, multilingual and multireligious features of the new state. The Slovenes were suddenly in a situation in which they identified themselves as people who talk with the same language and share unique culture, but at the same time identified themselves as part of the united Yugoslav nation. The aim of this study is to present the view of Slovene people on the Yugoslav identity and its influence on their self-determination. The study focuses primarily on the approach of the Slovenes towards their national identification. The first part of the study deals with the Slovene identity from the political discourse and the perspective of the Slovenes people’s party. The second part deals with the reflection of the Slovene shift towards nationalism in school policies and history textbooks.